Paleo-Hydrothermal Predecessor to Perennial Spring Activity in Thick Permafrost in the Canadian High Arctic, and Its Relation to Deep Salt Structures: Expedition Fiord, Axel Heiberg Island, Nunavut - Marcos Zentilli; Christopher R. Omelon; Jacob Hanley; Darren LeFort (Geofluids)
It is surprising to encounter active saline spring activity at a constant 6°C temperature year-round not far away from the North Pole, at latitude 79°24′N, where the permafrost is ca. 600 m thick and average annual temperature is -15°C. These perennial springs in Expedition Fiord, Queen Elizabeth Islands, Canadian Arctic Archipelago, had previously been explained as a recent, periglacial process. However, the discovery near White Glacier (79°26.66′N; 90°42.20′W; 350 m.a.s.l.) of a network of veins of hydrothermal origin with a similar mineralogy to travertine precipitates formed by the springs suggests that their fluids have much deeper circulation and are related to evaporite structures (salt diapirs) that underlie the area. The relatively high minimum trapping temperature of the fluid inclusions (avg. ~200 ± 45°C, 1σ) in carbonate and quartz in the vein array, and in quartz veins west of the site, explains a local thermal anomaly detected through low-temperature thermochronology. This paper reviews and updates descriptive features of the perennial springs in Expedition Fiord and compares their mineralogy, geochemistry, and geology to the vein array by White Glacier, which is interpreted as a hydrothermal predecessor of the springs. The perennial springs in Axel Heiberg Island are known for half a century and have been extensively described in the literature. Discharging spring waters are hypersaline (1-4 molal NaCl; ~5 to 19 wt% NaCl) and precipitate Fe-sulfides, sulfates, carbonates, and halides with acicular and banded textures representing discharge pulsations. At several sites, waters and sediments by spring outlets host microbial communities that are supported by carbon- and energy-rich reduced substrates including sulfur and methane. They have been studied as possible analogs for life-supporting environments in Mars. The vein array at White Glacier consists of steep to subhorizontal veins, mineralized fractures, and breccias within a gossan area of ca. 350 × 50 m. The host rock is altered diabase and a chaotic matrix-supported breccia composed of limestone, sandstone, and anhydrite-gypsum. Mineralization consists of brown calcite (pseudomorph after aragonite) in radial aggregates as linings of fractures and cavities, with transparent, sparry calcite and quartz at the centre of larger cavities. Abundant sulfides pyrite and marcasite and minor chalcopyrite, sphalerite, and galena occur in masses and veins, much like in base metal deposits known as Mississippi Valley Type; their weathering is responsible for brown Fe oxides forming a gossan. Epidote and chlorite rim veins where the host rock is Fe- and Mg-rich diabase. The banded carbonate textures with organic matter and sulfides are reminiscent of textures observed in mineral precipitates forming in the active springs at Colour Peak Diapir. Very small fluid inclusions (5-10 μm) in two generations of vein calcite (hexagonal, early brown calcite we denominate “cal1” lining vein walls; white-orange sparry calcite “cal2” infilling veins) have bulk salinities that transition between an early, high-salinity end-member brine (up to ~20 wt% NaCl equivalent) to a later, low-salinity end-member fluid (nearly pure water) and show large fluctuations in salinity with time. Inclusions that occupy secondary planes and also growth zones in the later calcite infilling (deemed primary) have Th ranging from 100°C to 300°C (n=120, average~200°C; independent of salinity), 2 orders of magnitude higher than average discharging water temperatures of 6°C at Colour Peak Diapir. Carbon isotope composition (δ13CVPDB) of the White Glacier vein array carbonates ranges from approximately -20 to -30‰, like carbonates formed by the degradation of petroleum, whereas carbonates at Colour Peak Diapir springs have a value of -10‰. Oxygen isotope composition (δ18OVSMOW) of vein carbonates ranges from -0.3‰ to +3.5‰, compatible with a coeval fluid at 250°C with a composition from -3.5‰ to -7.0‰. These data are consistent with carbonates having precipitated from mixtures of heated formational waters and high-latitude meteoric waters. In contrast, the δ18OVSMOW value for carbonates at Colour Peak Diapir springs is +10‰, derived from high-latitude meteoric waters at 6°C. The sulfur isotope (δ34SVCDT) composition of Fe-sulfides at the perennial springs is +19.2‰, similar to the δ34SVCDT of Carboniferous-age sulfate of the diapirs and consistent with low-temperature microbial reduction of finite (closed-system) sulfate. The δ34SVCDT values of Fe-sulfides in the vein array range from -2.7‰ to +16.4‰, possibly reflecting higher formation temperatures involving reduction of sulfate by organics. We suggest that the similar setting, mineralogical compositions, and textures between the hydrothermal vein array and the active Colour Peak Diapir springs imply a kinship. We suggest that overpressured basinal fluids expelled from the sedimentary package and deforming salt bodies at depth during regional compressional tectonic deformation ca. 50 million years ago (Eocene) during what is known as the Eurekan Orogeny created (by hydrofracturing) the vein array at White Glacier (and probably other similar ones), and the network of conduits created continued to be a pathway around salt bodies for deeply circulating fluids to this day. Fluid inclusion data suggest that the ancient conduit system was at one point too hot to support life but may have been since colonized by microorganisms as the system cooled. Thermochronology data suggest that the hydrologic system cooled to temperatures possibly sustaining life about 10 million years ago, making it since then a viable analogue environment for the establishment of microbial life in similar situations on other planets.